Analysis of Trends in Teaching Entrepreneurship for Masters of Education in the Czech Republic - Tadeush, Olena (Educological discourse, 2025)
The article identifies and summarises the trends in teaching entrepreneurship at master’s level in the Czech Republic for the period 2006–2025 at the European, national, and institutional levels and substantiates their characteristics. It is noted that the Czech Republic is one of the European countries that supports initiatives for entrepreneurship education in higher education institutions at the EU level, and is also a strategic partner of Ukraine in implementing the ideas of attractiveness in the content of educational programs for training specialists in various industries, which determined the choice of this country for studying relevant trends. The article describes and systematizes trends in teaching entrepreneurship for masters in the field of education in the Czech Republic according to the defined criteria: strategic-targeted, organizational-content, and resultbased-prognostic. The main trends of the strategic purpose are: implementation of the European strategy for entrepreneurship education at the level of EU member states, orientation on the EU regulatory framework; creation of a regulatory framework for the development of entrepreneurship in the country; supporting initiatives and projects for the development of entrepreneurship at the European, national, regional and local levels; developing and implementing state educational programs for teaching entrepreneurship to different segments of the population and at all levels of education in the country. Organizational and substantive trends include: compliance with the European framework for providing entrepreneurship education; cooperation with groups of coordinators engaged in entrepreneurship education at the EU level; launching and coordinating networks of simulation companies for entrepreneurship education; changing the concept of education in higher education institutions regarding the upbringing of entrepreneurship in the process of professional training of specialists in various fields; modernization of educational programs for professional training of specialists in the field of education in higher education institutions with the inclusion of sustainable and social entrepreneurship; involvement of leading specialists from the business sector (practitioners, entrepreneurs, graduates) in the educational process; implementation of elements of the dual education system in universities; support and guidance of educational institutions and graduate partners in creating their own businesses; expansion of strategic areas of entrepreneurial education by strengthening partnership cooperation between universities at the EU level. The main trends of the result-oriented and predictive purpose are: the spread of experience in teaching entrepreneurship to masters in the field of education; teaching entrepreneurship to teachers as one of the career options. It is noted that the experience of teaching entrepreneurship to masters in the educational field at universities in theCzech Republic can serve as a guideline for the modernization of relevant educational programs at universities in Ukraine.